Mathew Singleton report - Singleton, Mathew
Report by Singleton on the conduct of loyalists taken into custody during the Revolution in South Carolina. Includes list of prisoners.
Continental Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Continental Army; American loyalists -- South Carolina; South Carolina -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Prisoners and prisons; Army officers